GRAMMATICAL ANALYSIS ON THE ABSTRACT OF SCIENTIFIC WRITING - Madkur, Ahmad (JURNAL PEDAGOGY, 2013)
Abstract: This paper was aimed to investigate grammatical errors made in writing abstract for journals in State Islamic College (STAIN) Jurai Siwo Metro. It involved 30 abstracts taken from 5 journals published by the college. This research was qualitative in nature. The data were collected by observation and documentation, and then analyzed by Miles and Huberman model. The result showed that the frequency of grammatical errors in concord was 40%, word order was 25%, spelling was17%, parallel structure was 12 %, and learner language was 6%. To sum up, there were still some grammatical errors in the abstracts of scientific writing in the journals.Â Keywords: scientific writing, abstract, grammatical errors, journal